التوجه النسوي لحركة العصر الجديد - آساليبه وسبل مواجهته: دراسة تحليلية: (Feminist Orientation of the New Age Movement-Methods and Strategies for Confrontation: An Analytical Study) - Hamid Allah, Khaoula Saeed Al Arabi; Saged, Ali Ali Gobaili; Zainal Abidin, Azmil; Qatawneh, Mohammad Abdelhamid Salem (Online Journal of Research in Islamic Studies, 2024)
Preserving the role of women in society and empowering them with the status granted by Islamic teachings serve as a cornerstone for the sound development of the nation and safeguarding the fabric of the Muslim community. The significant cultural openness and the influx of globalization have facilitated the spread of feminist ideologies, particularly those of the New Age Feminist Movement, into Islamic societies. Given the apparent threat these ideologies pose to religious beliefs, it becomes imperative for specialists to confront and address this challenge. This research underscores the importance of identifying the essence of the New Age Feminist Movement, the mechanisms behind its dissemination, and the strategies to counter it. To achieve these objectives, the study adopts a critical analytical methodology and a survey approach, including a field study conducted among female students at Hassan II University in Morocco. The research presents a detailed examination of the nature of feminist ideologies, their origins, historical development, and the effects of feminist theories. It also explores their key objectives, distinguishing features, and fundamental pillars. Additionally, the study provides applied examples of how New Age Feminist ideologies propagate their ideas and pursue their goals. To complement the theoretical discussion, a field study was conducted to investigate the manifestations and reasons behind women abandoning Islam and turning to paganism. The findings reveal several key factors, including the pursuit of desires and whims, ignorance of and detachment from religion, uncritical adoption of Western paradigms without exploring sound Islamic principles, social and intellectual stagnation in contemporary Muslim societies, superficial religiosity, lack of firm religious foundations instilled by parents, and social upbringing. The study concludes with several recommendations, the most prominent being the urgent need to counter the influence of feminist ideologies, which dilute and distort authentic Islamic principles. This can be achieved by leveraging various educational and awareness tools, such as formal schooling, academic curricula, and media outlets, to confront these invasive ideas and protect the integrity of Islamic societies.